2017
DOI: 10.5603/fm.a2016.0029
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of melatonin on L-arginine-induced acute pancreatitis in adult male albino rats

Abstract: Background: Acute pancreatitis (AP) is an inflammatory disease that has an incre- Materials and methods: Thirty-six adult male albino rats were used in this study. Animals were divided into four groups; Control group (Group A; n = 6), Mel group (Group B; n = 6), L-arg group (Group C; n = 12) receiving two doses of L-arg injection with 1 h interval in-between, and L-arg+Mel group (Group D; n = 12) receiving Mel 1 h after each L-arg injection. 24 h after the second L-arg injection, the serum levels of amylase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…2017). Melatonin protects against Arg-induced AP in adult male Albino rats (Sadek and Khattab 2017). Inhibition of arginase activity ameliorated Arg-induced AP in Wistar rats (Biczó et al.…”
Section: Discussionmentioning
confidence: 99%
“…2017). Melatonin protects against Arg-induced AP in adult male Albino rats (Sadek and Khattab 2017). Inhibition of arginase activity ameliorated Arg-induced AP in Wistar rats (Biczó et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental studies have shown that pretreatment with melatonin could prevent pancreatic inflammation and radically reduce pancreatic tissue damage in rats subjected to acute pancreatitis in different experimental models [13,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73]. This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
“…This was evidenced by histological assessment of pancreatic tissue and prominent decline of the inflammatory markers, such as edema, neutrophil infiltration, and vacuolization of the acinar cells [60,61,62,63,73]. In animals with acute pancreatitis pretreated with melatonin, there was a significant reduction in the plasma morphometric indicators of pancreatic inflammation severity, blood levels of the enzymes, amylase and lipase, and blood levels of pro-inflammatory cytokines (e.g., TNFα, IL-1β, and IL-6), whereas anti-inflammatory interleukins IL-10 and IL-4 were increased [10,59,62,63,64,65,66,67,68,69,70]. The antioxidant effect of melatonin was expressed as a reduction of lipid peroxidation products (MDA + 4-HNE) in the pancreas and was accompanied by increased activity of antioxidant enzymes SOD, CAT, GPx, and GSH [62,63,64,65,66,67,69,70].…”
Section: Melatonin System and Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…They were after arrival from the supplier left for two weeks for acclimatization. Rats were fed a standard diet of commercial rat chow and tap water ad libitum through the time of the study (Sadek and Khattab 2017). The animal care and experiments protocol described in this study were complied with "Research Ethics Committee" Faculty of Medicine, Minia University, Egypt, which are in accordance with the NIH Guide for Care and Use of Laboratory Animals (U.S. Department of Health and Human Services, NIH 1992).…”
Section: Methodsmentioning
confidence: 99%